Optimizing maize seed assistance programs for enhanced productivity in Indonesia - Aditya Alta; Azizah Nazzala Fauzi; Binar Asri Lestari; Biyan Shandy; Deasy Pane; Hasran; Maria Dominika; Shabrina Tjandra (Center for Indonesian Policy Studies (CIPS), 2025)
Maize is important for the economy as its output is widely used as raw material and intermediate goods by downstream sectors such as feed (62.72%) and processed flour (11.40%). Additionally, maize is the agricultural sector with the third-highest value-added, after rice and palm oil. Compared to 2014-2019, annual maize productivity in the last five years has decelerated. Maintaining and improving productivity momentum is thus important. Improving the adoption of high-yielding seeds through seed assistance programs is a viable policy option. However, the Crop-Cutting Survey from Statistics Indonesia shows that farmers who received seed assistance had lower productivity than farmers who did not, with the productivity of assistance recipients declining between 2019 and 2022. This shows the urgency of evaluating the effectiveness and efficiency of seed assistance programs. Improvements in assistance targeting using a dataset to determine market status have resulted in more farmers independently adopting high-yielding seed varieties after the program and less market distortion. However, there is still substantial recipient leakage and marginal improvement in the overall program's benefit and cost ratio. To support maize productivity growth, the improvement of the seed assistance program needs to be comprehensive. This goes beyond expanding the implementation of area classifications based on market status and covers the planning, implementation, monitoring, and evaluation processes. This includes establishing integrated strategic planning, clear program objectives, seed adoption monitoring, accurate targeting, alignment with GAP assistance, and infrastructural support.
Keywords: 330